Evaluasi Kelayakan Instalasi Gedung TTSK 3 Lantai PT Phapros, Tbk Semarang - Efa Yumna Purwono (Energi & Kelistrikan, 2022)
The development of time and the increasing need for electricity, electrical installations must undergo changes both in quality and quantity. The decrease in the quality of electrical installations and changes in the quantity of load points can result in changes in the quality and quantity of installation feasibility and safety of the wearer. Therefore, checking and evaluating electrical installations is carried out. Research at the TTSK building of PT Phapros, Tbk determines predetermined criteria, including: earth resistance, insulation resistance, safety, and delivery cross-section. After meeting the criteria, installation testing is carried out. The result of the feasibility evaluation of the installation feasibility of PT Phapros 3 floor TTSK building, Tbk reached 92% feasible, and 8% unfit. These tests include testing of earth resistance with a decent number of 67%. From the results of testing on insulation resistance with a decent amount of 100%. From the safety of electrical installations with a decent amount of 100%, as well as the results of the cross-section of electrical installations with a decent amount of 100%.